Computer acceptance of older adults. - Soares, Marcelo M.; Jacobs, Karen; Nägle, Sibylle; Schmidt, Ludger (Work)
Even though computers play a massive role in everyday life of modern societies, older adults, and especially older women, are less likely to use a computer, and they perform fewer activities on it than younger adults. To get a better understanding of the factors affecting older adults' intention towards and usage of computers, the Unified Theory of Acceptance and Usage of Technology (UTAUT) was applied as part of a more extensive study with 52 users and non-users of computers, ranging in age from 50 to 90 years. The model covers various aspects of computer usage in old age via four key constructs, namely performance expectancy, effort expectancy, social influences, and facilitating conditions, as well as the variables gender, age, experience, and voluntariness it. Interestingly, next to performance expectancy, facilitating conditions showed the strongest correlation with use as well as with intention. Effort expectancy showed no significant correlation with the intention of older adults to use a computer.